PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN AGROWISATA DESA BANYUASIN KABUPATEN BANGKA - Novyandra Ilham Bahtera; Gogo Prayoga; Muhammad Ridho; Sary Wahyuni; Wirdayanti Wirdayanti; Rindiani Rindiani (Jurnal Abdi Insani, 2023)
Banyuasin Village, Bangka Regency, in the last five years has attempted to make Banyuasin Village an agricultural-based tourism village destination. The Banyuasin Village Government and the community continue to strive to find the best way to create a tourist village. Various kinds of programs have been implemented such as assistance from a team of experts. However, these efforts have not been optimal due to limited human resources in Banyuasin Village and not optimal awareness at the community level. So, the purpose of implementing this program is to increase awareness of the Tourism Awareness Group in the urgency of strong and professional institutions and to assist POKDARWIS and MSME actors in preparing agro-tourism villages. The method used in this community empowerment program is through a process of intensifying socialization about the importance of strengthening social solidarity and becoming agents of change. There are several main programs implemented in this empowerment program, namely: i) holding village fairs; ii) four programs from the Social Economy Division, Marketing Division, Finance Division, Fisheries Technology Division); and iii) establishment of a new POKDARWIS organization. This program obtained several results and findings, namely that the people of Banyuasin Village were enthusiastic in participating in every existing program. This is evident from a number of things such as: i) the formation of a new POKDARWIS management system with a management system that is better than before and accompanied by stronger internal strengthening of the institution; ii) increasing knowledge about village tourism through strengthening village internalization; iii) increasing community participation; iv) the re-establishment of inter-line social dynamics and solidarity in society; and v) formation of new skills and new knowledge possessed by the community. This program succeeded in achieving its goal of increasing POKDARWIS awareness through mentoring activities for users of the benefits of the community empowerment program.